Association of plasma retinol levels with incident cancer risk in Chinese hypertensive adults: a nested case–control study. Issue 3 (29th July 2019) - Xie, Liling; Song, Yun; Lin, Tengfei; Guo, Huiyuan; Wang, Binyan; Tang, Genfu; Liu, Chengzhang; Huang, Weitong; Yang, Yan; Ling, Wenhua; Zhang, Yan; Li, Jianping; et al.
Abstract: We aimed to investigate the association between plasma retinol and incident cancer among Chinese hypertensive adults. We conducted a nested case–control study, including 231 patients with incident cancer and 231 matched controls during a median 4·5-year follow-up of the China Stroke Primary Prevention Trial. There was a significant, inverse association between retinol levels and digestive system cancer (per 10 μg/dl increases: OR 0·79; 95 % CI 0·69, 0·91). When compared with participants in the first quartile of retinol (< 52·3 μg/dl), a significantly lower cancer risk was found in participants in quartile 2–4 ( ≥ 52·3 μg/dl: OR 0·31; 95 % CI 0·13, 0·71). However, there was a U-shaped association between retinol levels and non-digestive system cancers where the risk of cancers decreased (although not significantly) with each increment of plasma retinol (per 10 μg/dl increases: OR 0·89; 95 % CI 0·60, 1·31) in participants with retinol < 68·2 μg/dl, and then increased significantly with retinol (per 10 μg/dl increase: OR 1·65; 95 % CI 1·12, 2·44) in participants with retinol ≥ 68·2 μg/dl. In conclusion, there was a significant inverse dose–response association between plasma retinol and the risk of digestive system cancers. However, a U-shaped association was observed between plasma retinol and the risk of non-digestive cancers (with a turning point approximately 68·2 μg/dl).